Targeting Unconventional Pathways in Pursuit of Novel Antifungals - Nguyen, Stephanie; Truong, Jia Q.; Bruning, John B. (Frontiers in Molecular Biosciences, 2021)
The impact of invasive fungal infections on human health is a serious, but largely overlooked, public health issue. Commonly affecting the immunocompromised community, fungal infections are predominantly caused by species of Candida, Cryptococcus and Aspergillus. Treatments are reliant on the aggressive use of pre-existing antifungal drug classes that target the fungal cell wall and membrane. Despite their frequent use, these drugs are subject to unfavorable drug-drug interactions, can cause undesirable side-effects and have compromised efficacy due to the emergence of antifungal resistance. Hence, there is a clear need to develop novel classes of antifungal drugs. A promising approach involves exploiting the metabolic needs of fungi by targeted interruption of essential metabolic pathways. This review highlights potential antifungal targets including enolase, a component of the enolase-plasminogen complex, and enzymes from the mannitol biosynthesis and purine nucleotide biosynthesis pathways. There has been increased interest in the enzymes that comprise these particular pathways and further investigation into their merits as antifungal targets and roles in fungal survival and virulence are warranted. Disruption of these vital processes by targeting unconventional pathways with small molecules or antibodies may serve as a promising approach to discovering novel classes of antifungals.